PERSUASIVITY AND CREATIVE MESSAGE STRATEGY IN ADVERTISING (Marketing Journal, 2025)
This article examines the role of creative strategies in enhancing the effectiveness of advertising messages. It analyzes Charles F. Frazerʼs seven strategic approaches: generic, preemptive, unique selling proposition, brand image, positioning, resonance, and affective. Using local advertising examples, the impact of these strategies on audience perception and brand positioning is evaluated. A semiotic approach was applied to interpret the symbolic and visual elements in the messages. The findings show that strategically structured and creatively developed advertising content plays a significant role in strengthening brand success. 489
Keywords: advertising; advertising message; creative strategy; semiotic analysis; advertising communication; consumer psychology; advertising technology; brand image; audience perception